The treatment and the realization of the female prisoners’ rights in the correctional institution for women in Požarevac - Ćopić Sanja; Stevković Ljiljana; Šaćiri Bejan (Temida, 2012)
In order to enable the development of each individual and his/her reintegration and social inclusion after imprisonment, the state is obliged to guarantee certain rights to the prisoners as well as realization of these rights: the right to work, education, health care, social contacts, support and assistance, religious rights etc. These rights are guaranteed by relevant legal acts of the Republic of Serbia. However, women have special needs and requirements in comparison to male prison population. Due to that, the treatment of female prisoners should be gender sensitive. Taking that as a starting point, the action research of the Victimology Society of Serbia, which was conducted in 2011 and 2012, aimed at getting to know what is the level of respect of female prisoners’ rights in the Correctional Institution for Women in Požarevac and to what extent gender sensitive approach is present. The results of the research are presented in this paper.